A comparison Generation Methods for Non Homogeneous Poisson Process Model Using Simulation (Al-Mansour Journal, 2022)
Non Homogeneous Poisson process has property with wide application in most scientific fields specialty communication systems fields and engineering fields queuing theory and reliability theory and repairable systems and others the much from phenomenon's which attached occur it with change time.In this research, whole a comparison two methods for generate non homogeneous Poisson process is Melamed & Rubinstein method and Joe method, then whole the comparison to estimate parameters of power law model  (t) for NHPP in the maximum likelihood method for getting estimation power law model ˆ(t) and to next succeeding last model for two methods for generating NHPP for good style best two methods . Results gained to that mean square error for estimation power law model ˆ(t) and adopt on Melamed & Rubinstien generating method for NHPP is the best
Keywords: Melamed & Rubinstien Method; Joe Method